2019
DOI: 10.1016/j.oneear.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Securing Platinum-Group Metals for Transport Low-Carbon Transition

Abstract: Highlights d The impact of fuel cell vehicle deployment on platinum demand is evaluated d Platinum-group metals are not likely to be a constraint at the global level d The situations at regional and national levels are challenging d Innovative policies should be made to improve resource efficiency and security

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…These metals, characterized by high catalytic activities, are indispensable ingredients for fuel cells. The comparison of projected future global platinum group metal demand with resource endowment implies a less challenging future compared with the situation for lithium in a HDV electrification scenario 11 . It is therefore proposed that fuel cell vehicles should be prioritized for decarbonizing the HDV segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metals, characterized by high catalytic activities, are indispensable ingredients for fuel cells. The comparison of projected future global platinum group metal demand with resource endowment implies a less challenging future compared with the situation for lithium in a HDV electrification scenario 11 . It is therefore proposed that fuel cell vehicles should be prioritized for decarbonizing the HDV segment.…”
Section: Discussionmentioning
confidence: 99%
“…The lithium inflow, outflow, and stock associated with PEVs are simulated by using the Transport Impact Model (TIM) developed by the China Automotive Energy Research Center at Tsinghua University 11,14 . TIM is a technology-rich, bottom-up approached model that is used to simulate the energy, environmental, and resource impacts from the global transport sector.…”
Section: Methodsmentioning
confidence: 99%
“…This means that there is a difference between renewable energy and sustainable energy. The choice to encourage the use of renewable fuels for transport might have significant consequences for other resources, not only for land and water but also for scarce raw materials [9,71]. The Dutch policy to encourage the use of electricity for transport must also be seen in a broader context.…”
Section: Discussionmentioning
confidence: 99%
“…Access to materials, processes and natural resources will nearly always encounter natural limits [2]. Hao et al [9], for example, have shown that hydrogen fuel cell vehicles depend on the availability of platinum, a scarce natural resource with regional supply limitations. Recently, many studies have analyzed the effects of a shift from traditional transport fuels towards less CF-intensive fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation